Radial artery cannulation and reversible skin pallor after saline flushing. What do you do? - Fierro, Carmen; Vetrugno, Luigi; Maggiore, Salvatore Maurizio (Acta Biomedica Atenei Parmensis, 2023)
Radial artery cannulation is widely used in intensive care units. However, it is not free from risks. We cannulated the left radial artery in a 75-year-old man and observed this phenomenon but found poor information from literature searches. We propose that the pallor around the insertion site after flushing the line with saline may be due to the cold and high-pressure injection, causing localized superficial vasospasm. Luckily, skin pallor resolved once the arterial lavage was stopped. This phenomenon may be less observed by practitioners leading to underestimating the possibility of related complications.